Long-term seizure outcome in 211 patients with focal cortical dysplasia - Fauser, Susanne; Essang, Charles; Altenmüller, Dirk-Matthias; Staack, Anke Maren; Steinhoff, Bernhard J.; Strobl, Karl; Bast, Thomas; Schubert-Bast, Susanne; Stephani, Ulrich; Wiegand, Gert; Prinz, Marco; Brandt, Armin; et al. (Epilepsia, 2015)
Objective Focal cortical dysplasia (FCD) is currently recognized as the most common cause of neocortical pharmacoresistant epilepsy. Epilepsy surgery has become an increasingly successful treatment option. Herein, the largest patient cohort reported to date is analyzed regarding long-term outcome and factors relevant for long-term seizure control. Methods Two hundred eleven children and adults undergoing epilepsy surgery for histologically proven FCD and a follow-up period of 2-12 years were analyzed regarding the longitudinal course of seizure control, effects of FCD type, localization, magnetic resonance imaging (MRI), timing of surgery, and postoperative antiepileptic treatment. Results After 1 year, Engel class I outcome was achieved in 65% of patients and the percentage of seizure-free patients remained stable over the following (up to 12) years. Complete resection of the assumed epileptogenic area, lower age at surgery, and unilobar localization were positive prognostic indicators of long-term seizure freedom. Seizure recurrence was 12% after the first year, whereas 8% achieved late seizure freedom either following additional introduction of antiepileptic drugs (AEDs) (4%), a reoperation (2%), or a running down phenomenon (2%). Thirty-nine percent of patients had a reduction of AED from polytherapy to monotherapy or a complete cessation of AED treatment. Late seizure relapse was seen in nine patients during reduction of AEDs (i.e., in 12% of all patients with AED tapering); in four of them seizures persisted after reestablishment of antiepileptic medication. Significance Postoperative long-term seizure outcome was favorable in patients with FCD and remained stable in 80% of patients after the first postoperative year. Several preoperative factors revealed to be predictive for the postoperative outcome and may help in the preoperative counseling of patients with FCD and in the selection of ideal candidates for epilepsy surgery.